Output feedback based adaptive consensus tracking for uncertain heterogeneous multi-agent systems with event-triggered communication. (February 2022) - Long, Jiang; Wang, Wei; Wen, Changyun; Huang, Jiangshuai; Lü, Jinhu
Abstract: In this paper, a backstepping based distributed adaptive output feedback control scheme is proposed, to achieve output consensus tracking for uncertain heterogenous linear multi-agent systems with event-triggered communication and directed communication topology. To deal with the unknown system parameters while addressing the non-differentiability problem of the virtual control inputs, auxiliary systems are elaborately constructed for the agents with relative degree larger than one. Different from most of the existing results, both the system orders and the relative degree of all the agents are allowed to be nonidentical. To decrease the amount of communication, a decentralized triggering condition with time-varying triggering threshold is well designed such that continuous monitoring of neighboring states can be avoided. Besides, only the output of each agent needs be shared among neighbors, which contributes to further reduction of communication burden. It is shown that with the proposed control scheme, all the closed-loop signals are uniformly bounded and desired output consensus tracking can be achieved without Zeno behavior. Moreover, the tracking performance in the mean square sense can be improved by appropriately adjusting design parameters. Simulation results are shown to validate the effectiveness of the proposed control scheme.